Ulasan Pementasan Teater Sarah: Paradigma dalam Persembahan: Performance Review: The Paradigm in Performing of Theatre Sarah - Mohd Amir Mohd Zahari (Wacana Seni Journal of Arts Discourse, 2021)
The first performance of Sarah was presented at the School of Art, Universiti Sains Malaysia on 16 until 18 October 2019. Sarah’s script is the work of Noordin Hassan and directed by Halimi Mohamed Noh. The performance of Sarah is in-conjunction with the 90th anniversary of Malaysian National Laureate, Noordin Hassan. In critically evaluating theatre Sarah from the staging point of view, the production has achieved performance objectives, especially in terms of designing set and spectacle elements. Thus, this article further discusses Noordin Hassan’s patterns of thoughts through his work as well as the actions of the director in highlighting various aspects of staging Sarah.